Analysis and characterization of Cu2CdSnS4 quaternary alloy nanostructures deposited on GaN - Odeh, Ali Abu; Al-Douri, Yarub; Ameri, Mohammed; Bouhemadou, Abdelmadjid (Springer Verlag (Germany), 2018)
Through using spin coating technique, Cu2CdSnS4 (CCTS) quaternary alloy nanostructures were successfully deposited on GaN substrate using a wide range of spin coating speeds; 1500, 2000, 2500, 3000 and 3500 RPM at annealing temperature 300 °C. The optical properties were investigated through UV–vis which revealed the changing of energy band gap as the spin coating speed increases, in addition, to verify specific models of refractive index and optical dielectric constant. The structural properties were studied by X-ray diffraction which indicated that the number and intensity of the peaks were changed as the spin coating speed changes. The morphological and topographical studies of CCTS were elaborated by field emission-scanning electron microscopy and atomic force microscopy. The obtained results suggest that CCTS nanostructures deposited on GaN substrate are very suitable for optoelectronic applications, that are in accordance with the available theoretical and experimental data.